Dampak Pelatihan Pembuatan Pupuk Bokashi Untuk Petani Cabai Merah - Wardah, Eva; Maisura, Maisura; Budi, Setia (LPPM Universitas Malikussaleh - Indonesia, 2019)
This study aims to determine the impact of training to produce Bokashi fertilizer including; 1) the ability of red chili farmers as participants to identify raw materials to make Bokhashi fertilizer, 2) the farmers understand the benefits of Bokashi fertilizer in red chili cultivation, 3) the farmers are able to make Bokashi fertilizer, 4) farmers familiar how to apply Bokashi fertilizer in the red chili cultivation, (5) farmers have a desire to apply Bokashi fertilizer to the red chili cultivation. The research method is qualitative descriptive which measures the impact of implementing Bokashi fertilizer training by comparing the initial evaluation (pretest) with the final evaluation (posttest) of the knowledge, skills, and attitudes of farmers towards Bokashi fertilizer training. The results of the study indicate the impact of increasing aspects of knowledge, skills, and attitudes of participants from the indicators assessed in this research activity. It is expected that the government and other empowerment parties will provide a variety of empowerment methods (a combination of training and mentoring) to increase the knowledge, skills, and attitudes of farmers in farming chili